Superstitious Ideas of Coved 19 among students of Salahaddin University - Erbil - Saza Hussen Rasul; Diyar Mohialdeen Sadeq (Zanco Journal of Humanity Sciences)
The current research aims to identify The level of superstitious ideas of Coved 19 among students of Salahaddin  University - Erbil, and according to gender variables (males - females) and specialization variables (scientific - humanitarian), the research sample reached (560) male and female students, of which (160) as a primary research sample, and (400) male and female students for the final research sample, The search scale was prepared by the researchers and the number of its items was (37 items), and after verifying the psychometric properties of the scale (Face validity, Discrimination coefficient and   Reliability), the scale became in (27) items for the final application, the Reliability of scale  was extracted by two methods, Test and Re test way,  and  Alfa Cronbach way, after applying the scale to the final sample of the research, All statistics processing done by  using the statistical bag of social sciences (SPSS), the results showed that The level of superstitious ideas for Coved 19 among students of Salahaddin University - Erbil in general is high, and the level of superstitious ideas of Coved 19 for students (females) and  (humanities) are  more level.